Factors affecting Electronic Word-Of-Mouth (EWOM) adoption of restaurant reviews in Facebook / Zubaidah Mohd Ali Tan - Mohd Ali Tan, Zubaidah (2013)
The importance of internet is undeniable and the number of internet users keeps on increasing. In addition, the trend of social media usage in hospitality industry is becoming more obvious including from restaurant service industry. The Information Adoption Model is use to examine the factors that influenced the adoption of electronic word-of-mouth (eWOM) from social network site (SNS). Survey data collected from 305 users of Facebook indicated that argument quality and source credibility influenced the perceived information usefulness and information adoption. Comprehensiveness, Timeliness, Relevance, and Source Trustworthiness were significantly related to perceived information usefulness of restaurant reviews. The findings of the study also provide several insights for foodservice establishment.